NA’MATAK (ROSA CANINA L.) PLANTATSIYALARINI BARPO ETISH VA PARVARISHLASHNING TEXNOLOGIYASINI TAKOMILLASHTIRISH. - Xo’jaqulova Durdona Sadriddin qizi; Tursunova Parizoda Panjiboy qizi (TADQIQOTLAR, 2026)
This graduation qualification work studied the issues of improving the technology of establishing and maintaining plantations of Rosa canina L. The study analyzed the biological characteristics of the plant, agrotechnical requirements, planting schemes, and the effects of irrigation methods on productivity. Particular attention was given to the adaptability of the plant to soil and climatic conditions, as well as the possibility of obtaining high-quality medicinal raw materials. Recommendations were developed for the efficient organization of plantations, increasing yield, reducing labor costs, and applying environmentally sustainable technologies. The research results are important for the development of rosehip cultivation and for supplying high-quality raw materials to the pharmaceutical and food industries.